HYPEROSTOSIS IN MURAENESOX TALABONOIDES (BLEEKER) - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
Hyperossification has been observed in supra-occipital bones, some of thedorsal fin rays and vertebrae of eel Mnraenesox talabonoides (Bleeker), in all thespecimens above 82 cm.